Two novel species of Kirschsteiniothelia from Sichuan Province, China - Jin, Yan; Chen, Yanpeng; Tian, Wenhui; Liu, Jian-Kui; Maharachchikumbura, Sajeewa S. N. (Phytotaxa, 2024)
Sichuan Province is recognized as one of the richest biodiversity hotspots of plants and animals in the world. However, fungal diversity in this region has been largely overlooked, prompting us to investigate it further. During a long-term survey of fungal diversity, two morphologically similar hyphomycetous fungi were collected. Multi-locus phylogenetic analysis and morphological examinations confirmed that these two collections are new to the genus Kirschsteiniothelia, designated as K. pini sp. nov. and K. sichuanensis sp. nov. Both species showed significant differences in sequence identities of the ITS barcode. Additionally, Kirschsteiniothelia sichuanensis, collected from decaying branches of an unidentified woody plant, differs from the phylogenetically close species K. extensum by having shorter conidia. Kirschsteiniothelia pini, collected from decaying branches of Pinus sp., differs from phylogenetically close species K. aquatica by having shorter and wider conidia and from K. cangshanensis by having shorter conidiophores. The study provided detailed descriptions, photographs of the new species, and an updated phylogeny for Kirschsteiniothelia.